Lake Rezaiyeh: a specialised summer habitat for Shelduck and Flamingos - Savage, Christopher (Wildfowl, 1964)
Common Shelduck (Tadorna tadorna), to a lesser extent the Ruddy Shelduck (T. ferruginea), and the Greater Flamingo (Phoenicopterus ruber roseus) are summer visitors to Lake Rezaiyeh, in Iranian Azarbaijan, where they remain throughout the breeding season under conditions of extremely high salinity. In 1960 the Common Shelduck nested successfully in numbers but the Flamingo did not. The Common Shelduck were observed to congregate for their moult. The habitat is described in some detail, in particular the relationship between the lake salinity and the sole sources of food, the brine shrimp Artemia and the alga Enteromorpha intestinalis.